Jæʕne dans le discours des Libanais : pragmaticalisation, distribution et emplois d’un marqueur discursif déverbal - Layal Kanaan (Discours)
This paper deals with jæʕne, a Lebanese discourse marker (also used by Syrian, Palestinian and Egyptian speakers). Jæʕne can be translated as it means, that is to say, I mean, you mean, or even by a filled pause. The marker was found during a PhD research that aimed to study reformulations in conversations in French between Lebanese francophone speakers. The present study is motivated by the high frequency of jæʕne in the corpus and in the discourse of Lebanese speakers in general and by its link to the phenomenon of formulation/reformulation.The paper presents the evolution of the original verbal form into a conversational particle and proposes a distributional and functional study of its occurrences in the corpus.